The Tax Audit, Discrimination, and Machiavellianism in Indonesian - Michael, Michael (Penerbit Goodwood, 2025)
Purpose: This study investigates the impact of tax audits and tax discrimination on tax evasion among MSMEs in Indonesia, with a particular focus on the moderating role of Machiavellianism. Methodology/approach: A quantitative survey was conducted with 170 MSME actors in Tangerang using structured questionnaires. Data were analyzed using CB-SEM with Mplus 8.0. A quantitative survey was conducted with 170 MSME actors in Tangerang using structured questionnaires. Respondents were selected purposively, and data were analyzed using CB-SEM with Mplus 8.0 to examine the influence of tax audits, tax discrimination, and Machiavellianism on tax evasion. Results/findings: Tax audits and tax discrimination significantly increase tax evasion, especially among individuals with high Machiavellian traits. These findings highlight the importance of fairness, ethical awareness, and psychological considerations in designing effective tax compliance strategies. Conclusion: Tax audits and discrimination can backfire and raise evasion risks among Machiavellian individuals, indicating the need for psychologically informed tax strategies. Limitations: The study's use of convenience sampling in a single location limits generalizability. Future research should explore broader regions. Practical implications include risk-based audits, ethics education, and improved tax official professionalism. Contribution: Theoretically, the study integrates psychological factors into MSME tax compliance. Practically, it promotes fair policies and ethical approaches to reduce evasion and strengthen trust in the tax system.